Eksplorasi Bahan Alam sebagai Agen Pengikat Alternatif dalam Formulasi Sediaan Tablet - Muhammad Arif; M Ryza Hawary; Ferdi Riansyah; Rado Justeza; Iqbal Ibrahim; Lili Tazkiyah; Nadine Novita; Nurhayati; Maisya Salsabila; Zachri Al Hafis; Yones Paulus Sinaga (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: The manufacture of tablet formulations relied heavily on binding agents, but the high utilization of synthetic binders in the current pharmaceutical industry was associated with long-term safety concerns and elevated production costs. Objective: This study aimed to evaluate the excipient potential of natural materials, particularly starch derivatives and gum exudates, as more economical and environmentally friendly alternative binding agents. Methods: This study employed a Systematic Literature Review (SLR) method guided by the PRISMA protocol through Google Scholar, PubMed, and ScienceDirect databases within the 2022–2026 publication range, which retrieved 25 articles meeting the inclusion criteria. Results: The review results demonstrated that natural materials exhibited binding capacities comparable to standard synthetic polymers like PVP, and were proven to significantly enhance tablet hardness, reduce friability, while physical modifications such as pregelatinization successfully improved the flowability of native starch for the direct compression method. Conclusion: This study concluded that natural excipients held great potential as alternatives to commercial binders, although precise concentration optimization and purification process standardization were required to overcome raw material quality inconsistency.